Tra le pagine di scrittori e giornalisti–scrittori: una svolta stilistica, linguistica e interpretativa del calcio - Bacchetti, Flavia (Studi sulla Formazione/Open Journal of Education, 2023)
The contribution analyses diachronically the extent to which the subject of football was at the critical attention of writers and journalist-writers between the early 20th century and the 1970s. Football as a social phenomenon not only through interpretation and language, but also through the neo-capitalist evolution of society and the masses, between ideological-political instrumentalisation of the game and narrative metaphors.